FAM53A Affects Breast Cancer Cell Proliferation, Migration, and Invasion in a p53-Dependent Manner - Zhang, Jie; Sun, Mingfang; Hao, Miaomiao; Diao, Kexin; Wang, Jian; Li, Shiping; Cao, Qixue; Mi, Xiaoyi (Frontiers in Oncology, 2019)
Family with sequence similarity 53-member A (FAM53A) is an uncharacterized protein with a suspected but unclear role in tumorigenesis. In this study, we examined its role in breast cancer. Immunohistochemical staining of specimens from 199 cases of breast cancer demonstrated that FAM53A levels were negatively correlated with p53 status. In the p53 wild-type breast cancer cell line MCF-7, FAM53A overexpression inhibited cell migration, invasion, and proliferation, downregulated the expression of Snail, cyclin D1, RhoA, RhoC, and MMP9, and decreased mitogen-activated protein kinase kinase (MEK) and extracellular-signal regulated kinase (ERK) phosphorylation. Concurrently, it upregulated E-cadherin and p21 expression levels. Interestingly, opposite trends were observed in the p53-null breast cancer cell line MDA-MB-231. The MEK inhibitor PD98059 reduced the biological effects of FAM53A knockdown in MCF-7 cells and FAM53A overexpression in MDA-MB-231 cells, suggesting that FAM53A affects breast cancer through the MEK-ERK pathway. Silencing TP53 in MCF-7 cells and stably expressing wild-type p53 in MDA-MB-231 cells confirmed that the effects of FAM53A signaling through the MEK/ERK pathway depended on the p53 status of the cells. These results suggest that FAM53A acts as a tumor suppressor in p53-positive breast cancer by modulating the MEK-ERK pathway, but may be a potential candidate for targeted anticancer therapies in p53-negative breast cancer.